2018
DOI: 10.1007/s10508-018-1175-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link Between Daily Relationship Quality, Sexual Desire, and Sexual Activity in Couples

Abstract: Current models of sexual responding emphasize the role of contextual and relational factors in shaping sexual behavior. The present study used a prospective diary design to examine the temporal sequence and variability of the link between sexual and relationship variables in a sample of couples. Studying sexual responding in the everyday context of the relationship is necessary to get research more aligned with the complex reality of having sex in a relationship, thereby increasing ecological validity and taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 52 publications
(66 reference statements)
5
45
1
2
Order By: Relevance
“…Use of intimate apparel might also act as a form of self-arousal: a thorough review of women's sexual desire by Meana [55] suggests that women want to feel sexually desired. Although a main factor in the decline of sexual desire and overall functioning for women is the presence of children and increased roles and responsibilities [56][57][58], the current study found that women's parental status, employment status, income, and age were not predictors for the use of intimate apparel. We found the best predictors for women's use of intimate apparel during their most sexual encounter to be relative mate value, relationship commitment, and relationship satisfaction.…”
Section: Plos Onecontrasting
confidence: 67%
“…Use of intimate apparel might also act as a form of self-arousal: a thorough review of women's sexual desire by Meana [55] suggests that women want to feel sexually desired. Although a main factor in the decline of sexual desire and overall functioning for women is the presence of children and increased roles and responsibilities [56][57][58], the current study found that women's parental status, employment status, income, and age were not predictors for the use of intimate apparel. We found the best predictors for women's use of intimate apparel during their most sexual encounter to be relative mate value, relationship commitment, and relationship satisfaction.…”
Section: Plos Onecontrasting
confidence: 67%
“…Acknowledging that the menopause transition often undermines sexual functioning in women (Avis et al, 2017), we speculate that the importance postmenopausal women attribute to sexuality depends much more on relationship-oriented motivational processes than spontaneous (hormone-driven) sexual desire. Such motivational component of the female sexual response, including nonsexual motivation for sexual behavior, has already been postulated by Basson (2000) and shown in empirical studies for premenopausal women (Dewitte & Mayer, 2018). After having become widowed or divorced, downgrading the importance of sexuality may thus serve as an adaptive selfregulatory strategy (Gott & Hinchliff, 2003).…”
Section: Cohort Differences In Late-midlife Sexualitymentioning
confidence: 82%
“…These normative factors are likely to have played a particularly prominent role in the socialization of older age cohorts. However, as suggested by recent dyadic studies (Muise et al 2014;Dewitte and Mayer 2018), some of these sexuality-related gender differences may not be confined to older couples. Apart from the sociocultural influences, the potential disruptiveness of the male partner's less successful ageing for the couple's sexual life may also reflect physical (problematic male sexual function) and psychological issues (giving up sex due to a declining sense of masculinity; see Jowett et al 2012).…”
Section: Discussionmentioning
confidence: 93%